Fusion Molecules of Heat Shock Protein HSPX with Other Antigens of Mycobacterium tuberculosis Show High Potential in Serodiagnosis of Tuberculosis. - Ruqyya Khalid; Madeeha Afzal; Sana Khurshid; Rehan Zafar Paracha; Imran H Khan; Muhammad Waheed Akhtar (PLoS ONE, 2016)
Variable individual response against the antigens of Mycobacterium tuberculosis necessitates detection of multiple antibodies for enhancing reliability of serodiagnosis of tuberculosis. Fusion molecules consisting of two or more antigens showing high sensitivity would be helpful in achieving this objective. Antigens of M. tuberculosis HSPX and PE35 were expressed in a soluble form whereas tnPstS1 and FbpC1 were expressed as inclusion bodies at 37°C. Heat shock protein HSPX when attached to the N-termini of the antigens PE35, tnPstS1 and FbpC1, all the fusion molecules were expressed at high levels in E. coli in a soluble form. ELISA analysis of the plasma samples of TB patients against HSPX-tnPstS1 showed 57.7% sensitivity which is nearly the same as the expected combined value obtained after deducting the number of plasma samples (32) containing the antibodies against both the individual antigens. Likewise, the 54.4% sensitivity of HSPX-PE35 was nearly the same as that expected from the combined values of the contributing antigens. Structural analysis of all the fusion molecules by CD spectroscopy showed that α-helical and β-sheet contents were found close to those obtained through molecular modeling. Molecular modeling studies of HSPX-tnPstS1 and HSPX-PE35 support the analytical results as most of the epitopes of the contributing antigens were found to be available for binding to the corresponding antibodies. Using these fusion molecules in combination with other antigenic molecules should reduce the number of antigenic proteins required for a more reliable and economical serodiagnosis of tuberculosis. Also, HSPX seems to have potential application in soluble expression of heterologous proteins in E. coli.